The Science of Religion in Britain, 1860–1915. By Marjorie Wheeler-Barclay - Atherstone, Andrew (The journal of theological studies, 2012)
‘The End is Nigh for Oxford’s Theology Faculty’, proclaimed the headline in The Times newspaper (20 May 2011) as religious journalist Ruth Gledhill attempted an exposé of a confidential report mooting a shift in focus at Oxford University from ‘theology’ to ‘religious studies’. The blogosphere was quickly abuzz with ignorant cries of alarm that even in Oxford’s hallowed halls traditional Christian theology was being pushed aside by ‘multi-faith studies’ and ‘comparative religion’. Yet as Marjorie Wheeler-Barclay shows in her stimulating historical monograph, ‘comparative religion’ is not some trendy new-kid-on-the-block but has been established as an academic discipline—yes, even at Oxford—for the last century and a half.